Measuring Extractive Institutions: Colonial Trade and Price Gaps in French Africa - Federico Tadei (European Historical Economics Society (EHES), 2017)
A common explanation for current African underdevelopment is the extractive character of institutions established during the colonial period. Yet, since colonial extraction is hard to quantify, the magnitude of this phenomenon is still unclear. In this paper, I address this gap in the literature by focusing on monopsonistic colonial trade in French Africa. By using new archival data on export prices, I provide yearly-estimates of colonial extraction via trade, measured as the gap between actual prices that the colonial trading companies paid to African agricultural producers and prices that should have been paid in a counter-factual competitive market (i.e. world prices minus trade costs). The results show that African prices were about half than what they would have been in competitive markets. This suggests that colonial trade dynamics was characterized by a considerable amount of extraction.
Keywords: N17; O43; 330; Africa; Development; Extractive Institutions; Colonization; Trade; Price Gaps